UNIT COSTS IN INSTITUTIONS OF HIGHER EDUCATION. - Hungate, T. L. (The Accounting Review, 1934)
It is recognized that the total cost of higher education, whether in institutions publicly or privately supported, must finally be a charge upon the financial resources of the people. It is probable that institutional incomes will continue to be reduced for some time to come. It is important, therefore, to study expenditures with the view to assuring high standards for those desiring a college education at a cost which they can afford to pay. There are two great areas of economy open to institutions of higher education. The first is in the field of institutional coordination on a regional or state wide basis. The second great area of economy is in institutional internal administration. Somehow you must bring judgment to bear on the problem in order to provide the educational opportunities best suited to the greatest numbers and at the lowest possible cost. The educational services of colleges and universities may include instruction, research, and public service. Instruction is commonly provided in all institutions.